2014
DOI: 10.1017/s1352465814000484
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Attitudes towards Computerized Self-Help for Eating Disorders within a Community-Based Sample

Abstract: Online self-help for eating disorders is a desirable treatment option for many individuals. The information gathered regarding preferences in the type, medium, duration and frequency of support could be used in the development of future self-help strategies in order to maximize uptake, retention and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…Although screening and feedback about symptoms were less desirable components, there was a strong preference that material be tailored to the individual, even if that requires a screening process. Participants reported a preference for briefer sessions of online programs, consistent with previous findings [14]. However, there was a trade-off between duration and frequency, with a preference for delivery of brief sessions over shorter periods, but a preference for greater time between sessions when programs included longer sessions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Although screening and feedback about symptoms were less desirable components, there was a strong preference that material be tailored to the individual, even if that requires a screening process. Participants reported a preference for briefer sessions of online programs, consistent with previous findings [14]. However, there was a trade-off between duration and frequency, with a preference for delivery of brief sessions over shorter periods, but a preference for greater time between sessions when programs included longer sessions.…”
Section: Discussionsupporting
confidence: 85%
“…There has been limited research exploring user preferences for Internet interventions. A recent study by McClay and colleagues [14] in the area of online interventions for eating disorders has indicated that users had a preference for weekly engagement and sessions of 20 minutes or less. In a study of women with postpartum depression, 87.5% indicated a preference for intervention sessions of 15 to 30 minutes, whereas a third of women wanted videos to illustrate ways to cope and 65% wanted a chat room that was moderated by an expert in postpartum depression [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unguided interventions would have the additional advantage of allowing sufferers to retain a sense of anonymity, an attractive property for those who want to keep their eating disorder secret [36].…”
Section: The Use Of Etherapy Outside Healthcare Systemsmentioning
confidence: 99%
“…Such approaches are attractive due to greater potential cost-effectiveness, and evidence suggests that these alternative delivery methods are acceptable and feasible for delivery in this population (e.g., Carrard et al, 2011;Sanchez-Ortiz et al, 2011b). Recent evidence from McClay et al, (2016) indicated that online GSH programmes for bulimia were popular among a community sample of individuals presenting with bulimic symptoms, and the flexibility and regularity of support provided may be more important than offering guidance face-to-face. Indeed, for some, face-to-face contact is undesirable (McClay et al, 2013), with evidence to suggest that younger participants may be more comfortable in communicating and seeking support online (Kauer, Mangan & Sanci, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, some patients were dissatisfied with the amount of guidance offered and the level of expertise of the guide in addressing eating disorder symptoms (Banasiak et al, 2007;McClay et al, 2013). Indeed, participants particularly value guidance that is available frequently and easily, as demonstrated in a recent community survey of individuals with bulimic symptoms (McClay, Waters, Schmidt & Williams, 2016). Participants reported that the inclusion of regular, responsive, and remotely delivered support were desirable features of web-based self-help programmes for BN and BED (e.g., via text messaging, email or through forums; McClay et al, 2016).…”
mentioning
confidence: 99%